Living Apart Relationships in Contemporary Europe: Accounts of Togetherness and Apartness. (December 2014) - Stoilova, Mariya; Roseneil, Sasha; Crowhurst, Isabel; Hellesund, Tone; Santos, Ana Cristina
Drawing on a European cross-national biographical-narrative study of intimate life, this article discusses the complexity of experiences of 'togetherness' and 'apartness' amongst people in living apart relationships. We explore the five main ways in which interviewees spoke about and understood their current living apart relationships (as: chosen; temporary; transitional; undecided; and unrecognisable), which we argue shows the need for a broader conceptualisation of this form of intimate relationship than is suggested by the established notion of 'living apart together'. The article points to interviewees' varying experiences of receiving or being denied recognition and acceptance by others as belonging to a couple, as well as to their differing degrees of desire for, or rebellion against, expectations that living apart relationships should 'progress' towards cohabitation.